Handshake Feedback in a Haptic Glove Using Pouch Actuators - Yamaguchi, Seiya; Hiraki, Takefumi; Ishizuka, Hiroki; Miki, Norihisa (Actuators, 2023)
In this paper, we propose and demonstrate a haptic device with liquid-pouch motors that can simulate a handshake. Because handshakes involve contact of the palms or soft skin, handshake simulation requires the haptic device to provide pressure onto specific areas of the palm with soft contact. This can be achieved with thermally driven liquid-pouch motors, which inflate and deflate when a low-boiling-point liquid, here Novec™ 7000, evaporates and condenses, respectively. Due to the simplicity of the soft actuator system, this haptic glove is lightweight and conformable. To design the haptic glove, we experimentally investigated the contact region and strength in handshakes, which led to an optimal number, size and position for the liquid-pouch motors. Sensory experiments with human subjects verified that the designed haptic glove successfully simulated handshakes.